2015
DOI: 10.2147/ijn.s75557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on osteogenesis in vitro and osseointegration in vivo of carbon fiber-reinforced polyetheretherketone–nanohydroxyapatite composite

Abstract: As United States Food and Drug Administration-approved implantable material, carbon fiber-reinforced polyetheretherketone (CFRPEEK) possesses an adjustable elastic modulus similar to cortical bone and is a prime candidate to replace surgical metallic implants. The bioinertness and inferior osteogenic properties of CFRPEEK, however, limit its clinical application as orthopedic/dental implants. In this study, CFRPEEK–nanohydroxyapatite ternary composites (PEEK/n-HA/CF) with variable surface roughness have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…However, in the present study, early cell attachment and proliferation did not alter correspondingly with the increase in surface roughness. This result was in accordance with studies reported by Liao et al ( 44 ) and Deng et al ( 45 ). Therefore, superior hPDLSC responses on the PCL/PLGA scaffolds may be attained by modifying surface roughness with different ratios of PCL/PLGA.…”
Section: Discussionsupporting
confidence: 94%
“…However, in the present study, early cell attachment and proliferation did not alter correspondingly with the increase in surface roughness. This result was in accordance with studies reported by Liao et al ( 44 ) and Deng et al ( 45 ). Therefore, superior hPDLSC responses on the PCL/PLGA scaffolds may be attained by modifying surface roughness with different ratios of PCL/PLGA.…”
Section: Discussionsupporting
confidence: 94%
“…HA scaffold with a pore size of 200 μm is fully infiltrated by PEEK in both vertical (infiltration depth was 3 mm) and lateral directions, while maintaining the HA network structure and uniformity (Figure 3c). Both bioactive phase and PEEK matrix are fully interconnected, which is superior to existing techniques [20,21,22,23,24,25,26,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Different processing methods such as compounding and injection molding [17,18,19,20,21], compression molding [22,23,24,25], cold press sintering [26,27,28] and selective laser sintering (SLS) [29,30,31,32] have been used to produce bioactive PEEK/HA and β-TCP composites. Functionally graded PEEK/HA biocomposites can also be produced by layer-by-layer casting method [33].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the topographical surface properties of carbon-based nanomaterials could regulate the cells behaviors in two ways including; directly through affecting cytoskeleton or indirectly via protein alignment and unfolding (Lim and Donahue, 2007; Fraczek-Szczypta et al, 2015; Park and Im, 2015). It has been reported that the surface roughness could potentially increase the hydrophobicity of carbon-based nanomaterials' surface (Deng et al, 2015). In addition, the size of carbon-based nanomaterials could have a meaningful impact on the molecular and cellular responses (Fujita et al, 2015).…”
Section: Impact Of Physicochemical Properties On Cellular and Moleculmentioning
confidence: 99%